MANAJEMEN KEUANGAN DESA BERBASIS PARTISIPASI MASYARAKAT: STRATEGI TATA KELOLA KEUANGAN YANG BERKELANJUTAN - Tamsil; Rostiaty Yunus; Mariati (Journal Publicuho, 2025)
This study aims to comprehensively analyze village financial management in Bontoa Village, Maros Regency, with an emphasis on participatory practices in village budget management. The study adopted a descriptive qualitative approach with data collection through in-depth interviews, observation, and review of village documents. The findings show that community participation in village financial planning and monitoring is a determining factor in realizing fiscal transparency and efficiency. Despite challenges such as low financial literacy among villagers, structured reporting mechanisms and periodic village dialogues are key instruments in strengthening accountability. This article recommends the need for community-based fiscal education strategies and the integration of information technology as part of village financial governance reform.